Effect of the doping medium on blends of polyurethane and polyaniline - Malmonge, J. A.; Campoli, C. S.; Malmonge, L. F.; Kanda, DHF; Mattoso, LHC; Chierice, G. O. (Elsevier B.V., 2001)
Flexible and free-standing films from blends of polyurethane, based on castor oil, and polyaniline were obtained with various compositions by casting. Significant increase on conductivity followed by a considerable decrease on doping time was obtained by doping the films in N,N-dimethylformamide (DMF) solution with p-toluene sulphonic acid (TSA) or HCl instead of the conventional doping in aqueous solution. This doping efficiency is proposed to be due to an improved swelling of the blend structure caused by the solvent. The electrical conductivity increases significantly upon polyaniline content increase reaching 10(-2) S/cm for a polyaniline content of about 10% (w/w).
Keywords: conducting polymers; polyaniline; doping; blends; polyurethane